2004
DOI: 10.1111/j.1151-2916.2004.tb06341.x
|View full text |Cite
|
Sign up to set email alerts
|

Compression Deformation Mechanism of Silicon Carbide: I, Fine‐Grained Boron‐ and Carbon‐Doped β‐Silicon Carbide Fabricated by Hot Isostatic Pressing

Abstract: The deformation behavior of boron‐ and carbon‐doped β‐silicon carbide (B,C‐SiC) with an average grain size of 260 ± 18 nm containing 1 wt% boron was investigated by compression testing at elevated temperatures. Extensive grain growth during deformation was observed. The stress–strain curves were compensated for grain growth by assuming power‐law type of dependence on grain size and strain rate. The stress exponent n was ∼1.3 and the grain size exponent p was ∼2.7 at temperatures ranging from 1593° to 1758°C. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…These values compare well with previous results in LPS SiC containing Y 2 O 3 and Al 2 O 3 as sintering aids 12,29 and also for some SSS SiC. 14,17 As will be clear below, it is also important to note the duration of the tests: this was about 120 h for SiC-5YAG and more than 150 h for SiC-15YAG.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…These values compare well with previous results in LPS SiC containing Y 2 O 3 and Al 2 O 3 as sintering aids 12,29 and also for some SSS SiC. 14,17 As will be clear below, it is also important to note the duration of the tests: this was about 120 h for SiC-5YAG and more than 150 h for SiC-15YAG.…”
Section: Resultssupporting
confidence: 90%
“…3), in good agreement with previously reported values for SiC. 12,17,20,24 (3) Microstructure of the Deformed Materials side the creep machine during the tests but not loaded. It was also observed that cavitation was significantly more important in SiC-15YAG than in SiC-5YAG.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Since the equiaxed grains were maintained even after deformation, grain-boundary sliding is a major deformation mechanism of HIPed SiC. Shinoda et al 29 reported n 5 1.3 and p 5 2.7 in deformation of 1 wt% B, C-doped SiC, which was fabricated by HIPing at 980 MPa. These values were almost identical with our results on HIPed SiC.…”
Section: (2) Effect Of Oxygen Co-segregation On Grain Growthmentioning
confidence: 99%